Turma da Mônica em: abordagem de personagens com deficiência na perspectiva da inclusão para o ensino fundamental - Oliveira, Fernanda Marques de (2024)
There are several types of barriers present in the daily lives of people with disabilities, and the most significant are related to attitudes fueled by prejudice and ableism. To minimize this prejudice, anti-ableist information can be included in Elementary School content, in a playful way, through Comic Books (HQs). In this context, this work aims to propose an inclusive approach for Elementary School regarding the reading of Monica's Gang comic books, the result of research carried out in the Postgraduate Program in Basic Education Teaching, Master's Degree, PPGEEB, CEPAE/UFG. The work also has the following specific objectives: to analyze the anti-ableist potential of Monica's Gang comic books; to present an educational proposal for reading and interpreting texts, from the perspective of inclusion, for Elementary School teachers, which will constitute the educational product. To approach the proposed theme, the type of qualitative research will be used, with bibliographical research and documentary research. The state of the art consists of research carried out on the BDTD and CAPES platforms. For the analysis of the state of the art, the hypothesis is that there are no works that address anti-ableism in the comics of Turma da Mônica. For the analysis of the corpus of this research, the hypothesis is that although there is an attempt to address the inclusion of characters with disabilities in the comics of Turma da Mônica, the type of approach still often refers to the ableist bias, represented, most of the time, by the emphasis on the character's disability. The analysis of the comics has as its theoretical basis, mainly, Amaral (1998), Gonçalves; Albino; Vaz (2009), Vendramin (2009). The corpus of the research consists of fragments of seven comics involving characters with disabilities from Turma da Mônica and taken from the project of the Comptroller General of the Union - CGU “Um por todos e todos por um!” and two specific to the character André. The hypothesis resulting from the analysis of the corpus is that, although there is an attempt to address the inclusion of characters with disabilities in the Turma da Mônica comics, the type of approach still often refers to the ableist bias, represented, in most cases, by the person being taken for the disability. The educational product, entitled “Turma da Mônica em HQ X Ableism: reading and interpretation proposal for elementary school”, resulting from the proposed analyses, will be a book in digital format intended for elementary school teachers and will indicate guidelines for the work of reading and interpreting Turma da Mônica comics from the perspective of inclusion.